The relationship between entrapment and suicidal behavior through the lens of the integrated motivational-volitional model of suicidal behavior - O'Connor, Rory C. (Current opinion in psychology, 2018)
Suicide and suicidal behavior are major public health concerns. As a result, a number of psychological models have been developed to better understand the emergence of suicidal ideation and suicide attempts. One such model is the integrated motivational–volitional model, a tri-partite model of suicidal behavior, which posits that entrapment is central to the final common pathway to suicide. In this review, we summarize the extant research evidence for the relationship between entrapment and suicidal ideation and behavior. Although there is robust evidence for the relationship between entrapment and suicidal ideation and behavior, there are gaps in our knowledge. We discuss the clinical implications and suggest key directions for future research